(untitled) (Modern education and development, 2025)
In modern linguistics, increasing attention is being paid to the social, cultural, and communicative functions of language in human life and society. One of the key areas of focus is the study of terminology, not merely as lexical or grammatical units, but as conceptual elements intertwined with cultural reality. Among such terminological layers, food-related terms play a vital role in revealing the linguocultural resources of the Uzbek and English languages. The food culture, national dishes, and related terminology of any given nation reflect the worldview, historical development, and national identity of that people. This paper discusses the theoretical and methodological foundations of food terminology, exploring its structural, semantic, and cultural aspects within English and Uzbek. The interdisciplinary nature of food terminology is also emphasized, showcasing the necessity of integrating approaches from linguistics, cultural studies, sociolinguistics, and translation studies